Reconocimiento de las plagas y enfermedades en el cultivo de cacao (Theobroma cacao L.) en la parroquia Ricaurte, cantón San Lorenzo, Provincia de Esmeraldas 2019 - Palate Mazo, Ricardo Marcelo (2019)
SUMMARY The present investigation was carried out in order to determine the pests and diseases that affect the production of cocoa grown in the parish "Ricaurte" located in the canton San Lorenzo, Esmeraldas province at 36 msnm, and which control techniques apply to reduce the incidence of them in the production of cocoa beans. The primary information was taken by interviewing the producers in the area, who produce cocoa for more than 20 years, as the area has now become a cocoa producing area. In Ricaurte, they cultivate the varieties: CCN51, Fine de aroma and National, planted first for their production and the others for considering them native and resistant to pests and diseases. By means of the surveys and in the field it was possible to verify the gravel affectation of the monilia, produced by the fungus known as (Moniliophthora roreri); this fungus increases its reproduction especially in the wet season, damaging a large amount of fruit in its early stages of formation. To try to control this evil, the farmers perform pruning and collect the affected fruits, without achieving greater control; Another plague found is the sueldilla, witch's broom, and army ants are also identified as harmful to the cultivation of cocoa, likewise it was possible to identify which pests and in which state of the crop they most attack the cacao plant and its effect. Keywords: Pests, Disease, Cacao, Control.